Unconventional Photoconversion from In‐Plane 2D Heterostructures of 2D Transition Metal Carbides/Semiconductors. Issue 11 (1st September 2022) - Zhang, Bowei; Chu, Tianshu; Bai, Qi; Zhu, Chongqin; Francisco, Joseph S.; Xuan, Fuzhen
Abstract : 2D transition metal carbides/nitrides (MXenes) are thought of promising photothermal materials due to their broadband localized surface plasma resonance (LSPR) and attractive electromagnetic interference (EMI) properties. However, the weak oxidation resistance and unclear photothermal mechanism of MXenes impede their photothermal modulations. Herein, the in‐plane 2D Ti3 C2 /TiO2 heterostructures are fabricated by partial oxidation and an unconventional photothermal effect under near infrared irradiation, even if the oxidation compromises the EMI and LSPR capacities, is demonstrated. Such performance is ascribed to the faster transfer of photoexcited electrons across the seamless in‐plane Ti3 C2 /TiO2 heterointerface than the reported out‐of‐plane one, and the 1–2 orders of magnitude faster relaxation processes of electrons than the ground bleaching in the Original MXene. These experimental results are well‐supported by theoretical calculations. The conceptual advances broaden the fundamental understanding of the photoconversion of MXenes, which would be extended into a variety of applications, such as biomedical therapy, photosynthesis, and photovoltaics. Abstract : Photothermal conversion represents a key energy harvesting way for the prospect of a sustainable society. This work reports the super efficiency enabled by the faster injection of photoexcited electrons and the following relaxation processes in the seamless in‐plane Ti3 C2 MXene/semiconductor heterostructures. The unique charge dynamics show distinct advantages over the out‐of‐plane heterostructures and Original MXenes.